Review of Maqasid Syariah in Using Shopee PayLater - Imam Kamaluddin; Hasan Sulton (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines the use of Shopee PayLater as a payment method on the Shopee e-commerce platform from the perspective of maqashid sharia in Islam. Shopee PayLater offers convenience and flexibility in online shopping by providing instant loans that allow customers to receive goods first and PayLater or through installments. There are major risks, namely the potential for uncontrolled consumer behavior, which can lead to debt accumulation. In addition, the element of usury in the installment system and late fees charged by Shopee make this feature not entirely in line with Islamic economic principles. This research method is a literature review. The type of research used is library research (Library Research) research results. Shopee PayLater offers benefits in ease of transactions, its use needs to be done carefully and with careful consideration, especially in the context of sharia law. It is important for consumers to understand the risks associated with using this feature and ensure that the actions taken are not in accordance with Islamic teachings, because there are still many disadvantages in this transaction, especially in terms of safeguarding assets (hifzul maal) and avoiding practices that are contrary to sharia.